European Association of Urology Guidelines on Male Infertility: The 2012 Update - Jungwirth, Andreas; Giwercman, Aleksander; Tournaye, Herman; Diemer, Thorsten; Kopa, Zsolt; Dohle, Gert; Krausz, Csilla (European urology, 2012)
New data regarding the diagnosis and treatment of male infertility have emerged and led to an update of the European Association of Urology (EAU) guidelines for Male Infertility. To review the new EAU guidelines for Male Infertility. A comprehensive work-up of the literature obtained from Medline, the Cochrane Central Register of Systematic Reviews, and reference lists in publications and review articles was developed and screened by a group of urologists and andrologists appointed by the EAU Guidelines Committee. Previous recommendations based on the older literature on this subject were taken into account. Levels of evidence and grade of guideline recommendations were added, modified from the Oxford Centre for Evidence-based Medicine Levels of Evidence. These EAU guidelines are a short comprehensive overview of the updated guidelines of male infertility as recently published by the EAU (http://www.uroweb.org/guidelines/online-guidelines/), and they are also available in the National Guideline Clearinghouse (http://www.guideline.gov/). The updated European Association of Urology guidelines are based on evidence of the diagnosis and treatment of male infertility.